2017
DOI: 10.1017/slr.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Beyond East and West: Solidarity Politics and the Absent/Present State in the Balkans

Abstract: In this piece, we develop a more complex picture of the East-West divisions that have characterized much analysis of the region since the crisis began. By examining how differently positioned actors have responded, the migration flows become a heuristic for other important but less visible processes in post-socialist state formation and Euro-integration. We use the complexity of Serbia's reception as an empirical ground to create a new analytic framework that moves beyond over-simplified dichotomies. Doing thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Finally, the last Belgrade elections added another actor -Initiative Do not Drown Belgrade (Ne davimo Beograd, NDVBGD) as a leftist, citizens list. NDVB-GD has become recognizable to the wider public after a series of demonstrations against the Belgrade Waterfront project (Greenberg -Spasić 2017). This project is transforming and gentrifying a large space on the right bank of the Sava river in the centre of Belgrade, from a railway station and old industrial area to more residential and business usage.…”
Section: New Actors -Description and Analysis Of Tactical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the last Belgrade elections added another actor -Initiative Do not Drown Belgrade (Ne davimo Beograd, NDVBGD) as a leftist, citizens list. NDVB-GD has become recognizable to the wider public after a series of demonstrations against the Belgrade Waterfront project (Greenberg -Spasić 2017). This project is transforming and gentrifying a large space on the right bank of the Sava river in the centre of Belgrade, from a railway station and old industrial area to more residential and business usage.…”
Section: New Actors -Description and Analysis Of Tactical Issuesmentioning
confidence: 99%
“…The project is very important politically because it was an electoral promise of President Vučić and something that was very high on the political agenda. NDVBGD protested from the beginning of the project arguing that it was against public interest, against the legal framework and that it would decrease the quality of life in downtown Belgrade by serving only the interests of large capital (Greenberg -Spasić 2017). However, only after the Sava Mala incident) has this issue become very important and visible (Kmezić 2017).…”
Section: New Actors -Description and Analysis Of Tactical Issuesmentioning
confidence: 99%
“…183 These countries retain their historic status as borderlands, a situation reinforced by the character and events of the so-called migrant crisis, when the western Balkans became one of the most important routes for entry into the EU. 184 Reactions to that route, and the work done to close it, gave more meaning than ever to the idea of 'Fortress Europe', with much of the Balkans outside and subject to EU and national immigration laws. As a result, citizens in Western Balkan states have become increasingly disillusioned and disinterested, both in respect of their own state institutions, which are seen as ineffective 185 and also in respect of the EU, its institutions and its Member States.…”
Section: The Stalled Europeanisation Of Citizenship In South East mentioning
confidence: 99%
“…184 Reactions to that route, and the work done to close it, gave more meaning than ever to the idea of 'Fortress Europe', with much of the Balkans outside and subject to EU and national immigration laws. As a result, citizens in Western Balkan states have become increasingly disillusioned and disinterested, both in respect of their own state institutions, which are seen as ineffective 185 and also in respect of the EU, its institutions and its Member States. 186 Some have suggested that in Serbia, for example, Europeanisation has gone into reverse.…”
Section: The Stalled Europeanisation Of Citizenship In South East mentioning
confidence: 99%
“…183 These countries retain their historic status as borderlands, a situation reinforced by the character and events of the so-called migrant crisis, when the western Balkans became one of the most important routes for entry into the EU. 184 Reactions to that route, and the work done to close it, gave more meaning than ever to the idea of 'Fortress Europe', with much of the Balkans outside and subject to EU and national immigration laws. As a result, citizens in Western Balkan states have become increasingly disillusioned and disinterested, both in respect of their own state institutions, which are seen as ineffective 185 and also in respect of the EU, its institutions and its Member States.…”
Section: The Stalled Europeanisation Of Citizenship In South-eastmentioning
confidence: 99%